Stakeholders and issue management utilization in mining industry: Case study warehouse PT Freeport Indonesia - Pribadi, Jaisyalmatin; Arief, N. Nurlaela (International Journal Labs, 2024)
This research proposed the improvement of warehouse operations by employing a comprehensive analysis of stakeholders and implementing an issue management framework. The three-dimensional model of stakeholder identification and salience is applied to evaluate the attributes of power, legitimacy, and urgency among key stakeholders: customer, warehouse crew, and transportation crew. Utilizing tools like Empathy Map and Stakeholder Maps, the study gains insight into stakeholder perspectives and relationships within the material management environment. The analysis explains the crucial role of the warehouse crew in connecting and managing relationships. The Issue Management Framework, supported with Empathy Maps, is used to identify and address potential issues, while Stakeholder Maps aid in prioritizing solutions. The research concludes with a strategic plan and providing a holistic approach to potential challenges. The findings emphasize proactive measures to prevent stockouts and lateness of material services, proposing a direct material delivery system and regular training programs for customers to enhance understanding and reduce errors in material orders.